Hypothalamic‐pituitary‐adrenal axis differentially responses to morning and evening psychological stress in healthy subjects - Yamanaka, Yujiro; Motoshima, Hidemasa; Uchida, Kenji (Neuropsychopharmacology reports, 2019)
Aim The hypothalamic‐pituitary‐adrenal (HPA) axis responds to changing environmental demands including psychological stressors. The aim of the present study was to assess whether the time of day effects on the acute response of HPA axis activity to acute psychological stress. Method We studied 27 healthy young subjects. The subjects were participated two experiments as follows. In the first experiment, subjects were instructed to keep their regular sleep schedule for 2 weeks which were measured by using a wrist‐worn activity monitor. Afterward, to evaluate a diurnal rhythm of salivary cortisol, eight saliva samples were collected during waking period every 2 hours from when the subjects woke up. In the second experiment, the subjects were randomly assigned to two groups. The Trier Social Stress Test (TSST) was performed either in the morning (n = 14) or in the evening (n = 13). We measured diurnal rhythm of salivary cortisol and stress response of salivary cortisol and heart rate by the TSST. Morning and evening tests were started at 2 hours and 10 hours after woke up, respectively. Results All subjects showed a normal diurnal rhythm of salivary cortisol concentration, with a peak in the morning immediately after awaking and a minimum in the evening. The salivary cortisol response after the TSST was significantly increased from the prestress level in the morning but not in the evening. Conclusion The HPA response to acute psychological stress was more pronounced in the morning than in the evening, correlating with the circadian regulation of cortisol synthesis. The aim of the present study was to examine whether the HPA axis differentially responses to morning and evening psychological stressor in healthy subjects. Here, we could demonstrate that the HPA axis activity response to acute psychological stressor is higher in the morning than in the evening, relating with circadian rhythm of salivary cortisol concentration.